Knowledge of fertility and perception of fertility treatment among adults with sickle cell disease (KNOW FERTILITY) - Carrithers, Bria; Raja, Maidah; Gemmill, Alison; Cayton Vaught, Kamaria C.; Christianson, Mindy S.; Lanzkron, Sophie; Pecker, Lydia H. (Frontiers in Global Women's Health, 2023)
Introduction: This study assessed fertility knowledge in adults with sickle cell disease using the Cardiff Fertility Knowledge Scale and Fertility Treatment Perception Survey and compared knowledge scores in respondents with sickle cell disease to previously reported unaffected cohorts. Methods: This cross-sectional study surveyed adults over age 18 with sickle cell disease at an adult sickle cell disease center using a 35-question survey addressing infertility risk factor knowledge and perceptions of fertility treatment. Analyses included summary statistics for continuous and categorical variables, univariate linear regression, and Mann-Whitney U tests for group comparisons of Fertility Knowledge Scale scores. Fertility Treatment Perception Survey scores were measured by medians of the two positive statements and four negative statements to generate separate positive and negative treatment belief scores. Statistical significance was set at p < 0.05 for all analyses. Results: Ninety-two respondents (71 female, 21 male) with median age of 32 years (IQR: 25.0, 42.5) completed the survey between October 2020-May 2021. Sixty-five percent of respondents reported taking sickle cell disease treatment and 18% reported refusing at least one sickle cell disease treatment due to fertility concerns. The mean Fertility Knowledge Score was 49% (SD: 5.2), lower than reported in an international cohort (57% vs. 49%, p =0.001), and higher than in a cohort of reproductive-aged Black women in the USA (49% vs. 38%, p =0.001). Less than 50% of respondents correctly identified common infertility risk factors including sexually transmitted infections, advanced age, and obesity. Mean positive fertility perception score was 3 (IQR 3, 4), and negative fertility perception score was 3.5 (IQR 3, 4). Factors associated with agreement with negative fertility perception statements included: trying to conceive, refusing sickle cell disease treatment, and undergoing fertility treatment. Discussion: Opportunities exist to improve knowledge of infertility risk factors among adults with sickle cell disease. This study raises the possibility that one in five adults with sickle cell disease refuse SCD treatment or cure due to infertility concerns. Education about common infertility risks factors needs to be addressed alongside disease- and treatment- associated fertility risks.